Mycorrhiza-like structures in rooted microshoots of Pinus pinea L. - Castro, Mário Rui da Costa Basílio e (2012)
Pinus pinea L. (stone pine) is one of the major plantation species in Iberian Peninsula, being Portugal the largest edible seed producer in the world. The induction and improvement of in vitro rhizogenesis of microshoots of Pinus pinea was developed in our laboratory using a co-culture system with ECM fungi. In the acclimation phase in mixed substrates, or in rhizotrons, anatomical and morphological studies were done to observe the evolution of the root system in microshoots from the co-culture system vs. control plants. Extensive dichotomous and coralloid branching of lateral roots occurred spontaneously in inoculated and control plants as well. Moreover, similar branching occurred in liquid culture of excised seedling roots without the presence of ECM fungi. The striking similarity of these organs with pine ectomycorrhizas prompted their anatomical analysis; however the presence of Hartig net was not confirmed. These results suggested that the development of ECM-like structures might have occurred spontaneously.